2019
DOI: 10.1097/md.0000000000017809
|View full text |Cite
|
Sign up to set email alerts
|

The effect of contact needle therapy on fatigue in patients with cancer in palliative care

Abstract: Introduction: Almost all patients with end-of-life cancer experience cancer-related fatigue; however, there are only a few known effective coping methods.Objectives : We will conduct a prospective, multi-center, single-blinded randomized controlled study to evaluate the efficacy of acupuncture for cancer-related fatigue in patients with end-of-life cancer.Methods: We will enroll 120 patients with cancer hospitalized in a palliative care unit or receiving consultation from a palliative care team in four hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Acupuncture is an important CAM treatment modality and a substantial part of Traditional Chinese Medicine (TCM) [22]. Many studies have reported that acupuncture effectively relieves fatigue with various diseases [23][24][25]. However, the specific mechanism of acupuncture in treating fatigue in PD has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is an important CAM treatment modality and a substantial part of Traditional Chinese Medicine (TCM) [22]. Many studies have reported that acupuncture effectively relieves fatigue with various diseases [23][24][25]. However, the specific mechanism of acupuncture in treating fatigue in PD has not been clarified.…”
Section: Discussionmentioning
confidence: 99%